2013
DOI: 10.1152/ajpgi.00001.2013
|View full text |Cite
|
Sign up to set email alerts
|

A novel population of subepithelial platelet-derived growth factor receptor α-positive cells in the mouse and human colon

Abstract: Sanders KM. A novel population of subepithelial platelet-derived growth factor receptor ␣-positive cells in the mouse and human colon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
76
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(91 citation statements)
references
References 45 publications
14
76
0
Order By: Relevance
“…Moreover, in this study, and in several others, it was demonstrated that none of the CD34 and PDGFRα + cells were c-Kit labeled, definitively excluding that these cells are ICC (50)(51)(52)(53)(54)(55) (Figure 4). Notably, while in these reports (54,55) some cells located in the axes of the villi were PDGFRα + , Vannucchi et al (51) could not find any CD34 positive cells at this level. Under TEM, cells with the features of TC were described in the axes of the villi and called myoid cells (56)(57)(58).…”
Section: Tc Identification By Immunohistochemistry (See Table 1)supporting
confidence: 67%
See 3 more Smart Citations
“…Moreover, in this study, and in several others, it was demonstrated that none of the CD34 and PDGFRα + cells were c-Kit labeled, definitively excluding that these cells are ICC (50)(51)(52)(53)(54)(55) (Figure 4). Notably, while in these reports (54,55) some cells located in the axes of the villi were PDGFRα + , Vannucchi et al (51) could not find any CD34 positive cells at this level. Under TEM, cells with the features of TC were described in the axes of the villi and called myoid cells (56)(57)(58).…”
Section: Tc Identification By Immunohistochemistry (See Table 1)supporting
confidence: 67%
“…In humans, although all the CD34 positive cells were found to be also PDGFRα + , in the axes of the villi there were described only as PDGFRα + cells (51,54,55,63). In the muscle wall of humans and rodents the PDGFRα + cells also expressed the SK3 channel (see above) but, in the mouse, these PDGFRα/SK3 + cells were CD34 negative (60).…”
Section: Tc Subtypesmentioning
confidence: 98%
See 2 more Smart Citations
“…Recently, a new class of fibroblastlike cells expressing platelet derived growth factor receptor α (PDGFRα) have been described in the subepithelial layer of the gastrointestinal tract [38] . As has been demonstrated in both the murine detrusor muscle and colon, these cells express P2Y 1 receptors coupled to SK channels, leading to purinergic inhibition [39][40][41] .…”
Section: Intracellular Signaling Cascade Following Purinergic Receptomentioning
confidence: 99%